Economic evaluation alongside a randomised controlled trial to assess the effectiveness and cost-effectiveness of acupuncture in the management of chemotherapy-induced peripheral neuropathy. Issue 1 (February 2021) - Molassiotis, Alex; Dawkins, Bryony; Longo, Roberta; Suen, Lorna KP; Cheng, Hui Lin; Mok, Tony; Hulme, Claire T; Yeo, Winnie
Objective: To assess the cost-effectiveness of acupuncture in the management of chemotherapy-induced peripheral neuropathy (CIPN) in Hong Kong. Methods: A within trial cost-utility analysis with the primary endpoint for the economic evaluation being the Quality Adjusted Life Year (QALY) and associated Incremental Cost Effectiveness Ratio (ICER) over 14 weeks of treatment. A secondary cost-effectiveness analysis was undertaken with the endpoint being change in pain as measured on the Brief Pain Inventory (BPI). Results: Eighty-seven patients were randomised to acupuncture or usual care. Acupuncture resulted in significant improvements in pain intensity (8- and 14-week mean changes compared to usual care of −1.8 and −1.8, respectively), pain interference (8- and 14-week mean changes compared to usual care of −1.5 and −0.9, respectively) and indicators of quality of life and neurotoxicity-related symptoms. However, in the economic evaluation there was little difference in QALYs between the two arms (mean change 0.209 and 0.200 in the acupuncture and usual care arms, respectively). Also, costs yielded deterministic ICERs of HK$616, 965.62, HK$824, 083.44 and HK$540, 727.56 per QALY gained from the health care provider perspective, the societal perspective and the patient perspective, respectively. These costs are significantly higher than the cost-effectiveness threshold of HK$180, 450 that was used for the base case analysis. Conclusion: While acupuncture can improve symptoms and quality of life indicators related to CIPN, it is unlikely to be a cost-effective treatment for CIPN-related pain in health care systems with limited resources. Trial registration number: NCT02553863 (ClinicalTrials.gov) post-results.